2016
DOI: 10.1111/iej.12676
|View full text |Cite
|
Sign up to set email alerts
|

Effect of irrigation on surface roughness and fatigue resistance of controlled memory wire nickel‐titanium instruments

Abstract: Except the HyFlex files immersed in NaOCl, the surface roughness of other files exposed to irrigants increased. However, a change in the surface tomography of CM wire instruments caused by contact with irrigants for 10 min did not trigger a decrease in cyclic fatigue resistance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
26
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 33 publications
3
26
1
1
Order By: Relevance
“…These numbers are in average with the numbers recorded by Yılmaz and Ozyürek (34) . Our results were much higher than the numbers recorded by Cai et al, (6) where they tested new and immersed hyflex files for 10 minutes in NaOCl 5.25% and less than Shen etal., (35) where they tested typhoon CM files after immersion in 6% NaOCl for 25 minutes. The difference in numbers which is not high may be attributed to the difference in file design between the typhoon and the Mpro.…”
Section: Discussioncontrasting
confidence: 75%
See 1 more Smart Citation
“…These numbers are in average with the numbers recorded by Yılmaz and Ozyürek (34) . Our results were much higher than the numbers recorded by Cai et al, (6) where they tested new and immersed hyflex files for 10 minutes in NaOCl 5.25% and less than Shen etal., (35) where they tested typhoon CM files after immersion in 6% NaOCl for 25 minutes. The difference in numbers which is not high may be attributed to the difference in file design between the typhoon and the Mpro.…”
Section: Discussioncontrasting
confidence: 75%
“…File at body temperature will show martensitic R-phase and austenitic structure. (4) Cyclic fatigue fracture, the leading cause of instrument fracture occurs when the file rotates in a curved root canal in repetitive cycles of extension and compression in region of highest bending stress (5,6) . Gambarini et al2008 (7) , Praisarnti et al (8) and Zender (9) stated that fatigue resistance is of NiTi rotary is affected by material properties, cross-sectional design, metal surface treatments, metallurgical characterization and root canal irrigants.…”
Section: Introductionmentioning
confidence: 99%
“…In clinical practice, it is important to be aware of the effects of frequently used solutions on the surfaces of NiTi rotary files. Many studies have investigated the effects of irrigants on NiTi rotary files (Cai, Tang, & Ge, ; Prasad, Sam, & Arvind Kumar, ; Topuz et al, ). However, there have been no studies of the effects of irrigants on the surface properties of HyFlex EDM files manufactured using new EDM technology.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have used AFM to examine the effects of irrigants on the surface porosity of NiTi files and reported quantitative values and 3‐D images (Ametrano et al, ; Cai et al, ; Sağlam et al, ). In the present study, we used AFM to qualitatively and quantitatively examine changes in the surfaces of NiTi files after immersion in NaOCl and EDTA solutions.…”
Section: Discussionmentioning
confidence: 99%
“…However, a high risk of instrument fracture while removing root canal filling materials has been reported (Giuliani, Cocchetti, & Pagavino, ). Research on the surface topography of endodontic files demonstrated alterations after root canal preparations (Ozyurek, Yilmaz, Uslu, & Plotino, ), sodium hypochlorite immersion (Cai, Tang, & Ge, ), and multiple autoclave cycles (Yılmaz, Uslu, Özyürek, ). To date, only one study (Can Saglam & Gorgul, ) in the literature has evaluated surface alterations of endodontic files after removing root canal filling material.…”
Section: Introductionmentioning
confidence: 99%